Seroprevalence of erythrovirus B19 IgG among Saudi blood donors in Makkah, Saudi Arabia - Ayman K Johargy (Wolters Kluwer Medknow Publications, 2009)
Objectives: To determine the seroprevalence of immunoglobulin G (IgG) to erythrovirus B19 in Saudi blood donors in Makkah. Saudi Arabia. Subjects and Methods: A total of 578 blood (serum) samples were tested for erythrovirus B19-specific-IgG antibody among Saudi blood donors in Makkah. Saudi Arabia. Results: Erythrovirus B19-specific-IgG antibodies were detected in 441/578 (76.3%) of Saudi blood donors of different age groups. Conclusion: This study indicated that 76.3% of Saudi blood donors in Makkah city, Saudi Arabia, had been exposed to erythrovirus B19. This result is in accordance with previous studies performed in other countries.